Modelo de automação de testes funcionais para desenvolvimento ágil de software - (:unkn) unknown (Universidade Federal do Amazonas, 2013)
For some time, the professional software development companies are looking for new technical alternatives in order to optimize their processes, to deliver products to market as soon as possible and to meet customer expectations, increasingly demanding and intolerant of software failures. In this sense, the agile software development is gaining more space and consequently the software testing area which was previously considered a separate phase of development has changed over time to adapt to this new reality. The test automation activity is seen as key of agile development, but many teams still don t know how it should be done, who should take responsibility and run it and the correct procedures for this activity to be successful. Although the literature mentions about the particularities activities and best practices in this scenario, there are few related works and lack of experience reports or case studies that show, in practice, examples of use this from start to finish the automation strategy adopted. This paper aims to contribute to improving the quality of agile processes, and proposes an approach that involves the application of agile manifesto values in the activities of test automation, which can be used regardless of agile methodology adopted. In this study, observations were made on empirical about testing practices in agile projects developed at Nokia Technology Institute (INdT) and an experimental implementation of this approach at the Center for Electronic and Information Technology (CETELI), Federal University of Amazonas (UFAM). Experimental reports are available with different strategies for the automation of software testing and identification of some important issues to deal with difficulties in adapting testers and developers in this new scenario.
Keywords: Automação de teste; Teste de software; Desenvolvimento ágil; Teste de software ágil; Test automation; Automation testing; Agile development; Software testing; Agile testing; ENGENHARIAS: ENGENHARIA ELÉTRICA